Bamboo Charcoal as Solid-Phase Extraction Adsorbent for the Simultaneous Enrichment and Sensitive Determination of Copper and Lead in Environmental Samples - Wang, Xia; Sun, Jing; Zhao, Ru-Song; Wang, Xi-Kui (Asian Journal of Chemistry, 2013)
In this paper, the potential of bamboo charcoal as solid-phase extraction (SPE) adsorbent for the enrichment and determination of heavy metals at trace level in environmental water samples has been investigated. Cu2+ and Pb2+ were selected as the model analytes and inductively coupled plasma atomic emission spectrometry (ICP-AES) for the detection. Important factors affecting enrichment efficiencies of the analytes, such as sample pH, elution concentration and its volume, flow rate of sample, sample volume and interfering ions, have been investigated. The proposed method has been successfully applied for the enrichment and determination of trace heavy metals in environmental samples with satisfactory results.